From emotional map to design criteria: verification of the correlation between community green space form and emotional health of high-density urban residents - Zhang, Tianyi; Wang, Xukui; He, Junping (Frontiers in Public Health, 2025)
IntroductionRising public health awareness, driven by economic growth, underscores emotional health as a critical determinant of overall well-being. High-density urban development in Hong Kong’s Central and Western District severely limits accessible green spaces, exacerbating urban stress. This study investigates how tailored community green space design can mitigate this stress and enhance mental well-being by positively influencing residents’ emotions.MethodsUsing isovist analysis and Grasshopper simulation, an emotional map reflecting residents’ sentiments across the district was generated. User preferences for green space characteristics (richness, flower-to-grass ratio, connectivity, and shape) and their emotional impacts were quantitatively analyzed using 455 validated questionnaires.ResultsKey findings include: (1) Landscape Preference: The public favors medium-density landscapes and regularly shaped green spaces. (2) Emotion Regulation: Higher flower proportions enhance exhilaration, while greater green coverage promotes relaxation. Curved layouts stimulate exhilaration, whereas rectangular shapes and moderate connectivity facilitate relaxation. (3) Demographic Variations: Young people prefer highly connected “exploration spaces,” while the older adults favor tranquil spaces with higher flower-to-grass ratios and low density. Women express more positive emotions in green spaces, while men typically exhibit neutral responses.DiscussionThe study demonstrates that strategically designed green spaces—considering density, floral elements, geometry, and connectivity—can effectively regulate emotions and alleviate urban stress. Age- and gender-specific preferences highlight the need for inclusive design approaches. These findings provide actionable insights for therapeutic landscape interventions, promoting community well-being and informing sustainable urban development in high-density contexts.